2021
DOI: 10.3389/fcell.2021.711348
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Molecular Subtypes in Head and Neck Squamous Cell Carcinoma With Distinct Prognosis and Treatment Responsiveness

Abstract: Head and neck squamous cell carcinoma (HNSCC) is one of the most aggressive malignancies with complex phenotypic, etiological, biological, and clinical heterogeneities. Previous studies have proposed different clinically relevant subtypes of HNSCC, but little is known about its corresponding prognosis or suitable treatment strategy. Here, we identified 101 core genes from three prognostic pathways, including mTORC1 signaling, unfold protein response, and UV response UP, in 124 pairs of tumor and matched normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Sen et al recognized 2 prognostic and clinical immune subtypes of HNSCC, which differed in various aspects of prognosis, clinical outcomes, immune features, mutation pattern, biological functions, and response to immune checkpoint blockade therapy 22 . Zhang et al characterized 3 HNSCC subtypes with different molecular profiles and survival outcomes and proposed therapeutic drugs that might be suitable for specific subtypes 23 . Therefore, the exploration of individualized treatment modalities for HNSCC based on molecular subtypes is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sen et al recognized 2 prognostic and clinical immune subtypes of HNSCC, which differed in various aspects of prognosis, clinical outcomes, immune features, mutation pattern, biological functions, and response to immune checkpoint blockade therapy 22 . Zhang et al characterized 3 HNSCC subtypes with different molecular profiles and survival outcomes and proposed therapeutic drugs that might be suitable for specific subtypes 23 . Therefore, the exploration of individualized treatment modalities for HNSCC based on molecular subtypes is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we established a baseline for the examination of intra-tumoral heterogeneity and the detection of distinct molecular phenotypes in HNSCC using WGCNA, GO, and KEGG enrichment analysis. profiles and survival outcomes and proposed therapeutic drugs that might be suitable for specific subtypes 23 . Therefore, the exploration of individualized treatment modalities for HNSCC based on molecular subtypes is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the consensus molecular subtypes were established using “ConsensusClusterPlus” package in R software ( Wilkerson and Hayes, 2010 ). In head and neck squamous cell carcinoma, the molecular features of different subtypes were evaluated for potentially effective therapeutic agents ( Zhang et al, 2021 ). In gastric cancer, consensus molecular subtypes were associated with immune infiltration for prediction of survival ( Yu et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…For further explanation of whether these ZNFs were associated with more aggressive forms of HNSCC, we analyzed their expression profile in different molecular subtypes. We observed that all examined ZNFs were upregulated in the mesenchymal and less aggressive, atypical [ 30 ] tumors.…”
Section: Discussionmentioning
confidence: 99%